Treatment Outcomes of Topical Calcineurin Inhibitor Therapy for Patients With Vitiligo - Sutarti, Sutarti; Nadia, Nadia (International Medical Journal Corp. Ltd, 2024)
Background: The literature on topical calcineurin inhibitors (TCIs) for the treatment of vitiligo highlights their promising role as an alternative to traditional therapies. Literature Review: The comparative study by established that the combination of narrowband ultraviolet B (NB-UVB) therapy with 0.1% tacrolimus is both efficacious and safe, especially for localized vitiligo affecting less than 30% of the body surface area. The rapid onset of pigmentation, observed within 4-8 weeks, underscores the immunomodulatory properties of tacrolimus, which enhances melanocyte activity by inhibiting pro-inflammatory cytokines. This study laid the groundwork for further investigations into the mechanisms and effectiveness of TCIs in vitiligo treatment. Conclusion: In conclusion, the body of literature indicates that topical calcineurin inhibitors represent a significant advancement in the management of vitiligo. Their immunomodulatory properties, safety profile, and potential for combination therapies position them as effective treatment options. However, the need for further research to establish robust clinical guidelines and optimize treatment protocols remains evident.